Electoral Uncertainty, Fiscal Policies & Growth: Theory and Evidence from Germany, the UK and the US - George Economides; Jim Malley; Apostolis Philippopoulos; Ulrich Woitek (Center for Economic Studies and ifo Institute (CESifo), 2003)
In this paper we study the link between elections, fiscal policy and economic growth/fluctuations. The set-up is a dynamic stochastic general equilibrium model of growth and endogenously chosen fiscal policy, in which two political parties can alternate in power. The party in office chooses jointly how much to tax and how to allocate its total expenditure between public consumption and production services. The main theoretical prediction is that forward-looking incumbents, with uncertain prospects of re-election, find it optimal to follow relatively shortsighted fiscal policies, and that this lowers economic growth. The model is estimated using quarterly data for Germany, the UK and the US from 1960 to 1999. Our econometric results provide clear support for the main theoretical prediction. They also give plausible and significant estimates for the productivity of public production services, the weight which households place on public consumption services relative to private consumption and the time discount rate. Moreover, we find that changes in electoral uncertainty produce the longest lasting fluctuations in the European economies followed by the US.
Keywords: 330; political uncertainty; economic growth and fluctuations; optimal policy